Australia's transition to management of myrtle rust - C. Howard; V. Findlay; C. Grant (Journal of Forest Science, 2015)
Puccinia psidii sensu lato was detected in Australia in 2010 causing myrtle rust. A nationally cost-shared eradication program was conducted based on well-established emergency response arrangements for incursions of emergency plant pests into Australia, but it was ultimately decided that the pest was not eradicable from Australia. At this time, no formal mechanisms existed to provide a clear path for decision making and cost-sharing when transitioning from an eradication focus to long-term management of a plant pest. In 2011, the Australian Government established and funded a set of pilot transition to management programs for a number of noneradicable pests, one of which was for the myrtle rust pathogen, with the goal of using the outcomes of the pilot programs to guide the ongoing development of formal transition arrangements.